Estimation of H2O2 Content in Free Radical Bromination and Oxidation Reactions by the H2O2-HBr System Generated Effluent Samples by Iodometry Method - Tirumala Rao, K.; Mohan, Y.V.; Naveen; Vaikunta Rao, L. (Asian Journal of Chemistry, 2013)
A simple accurate and precise green analytical iodometric titration method was optimized for the estimation of hydrogen peroxide (H2O2) content in free radical bromination and oxidation reactions by using hydrogen peroxide (H2O2) and hydrogen bromide (HBr) system generated effluent samples. These process generated effluents are containing good amount of H2O2 and HBr reagents. Hydrogen peroxide will react rapidly with other compounds found air and if released to soil, will be broken down by reacting with other compounds. Hence the estimation of H2O2 is very crucial and important towards the protection of the environment. In view of this we have applied iodometry for this system. During straightforward analysis with KMnO4 titration method was not helpful to estimate the H2O2 content in this system and USP general chapters thiosulphate standardization by iodometry method was also attempted, which is not helping to estimate the H2O2 in the system again. The same iodometry titration method was attempted in presence of sulphuric acid medium which is encouraging accurate estimation of H2O2 content in bromination and oxidation reactions by using H2O2 and HBr process generated effluents.